Outbreaks of verminous bronchopulmonitis among sheep and goats in Himachal Pradesh - Asrani, R K; Batta, M K; Katoch, R C; Jithendran, K P; Sharma, Mnadeep; Singh, S P; Gupta, V K (The Indian Journal of Animal Sciences, 2012)
The detailed investigations on 5 outbreaks of verminous bronchopulmonitis in peak winter among migratory Gaddi sheep and goats in Himachal Pradesh were described. The clinical symptoms, gross lesions and histopathological alterations were studied. The concurrent ailments due to nematodes i .e. Dictyocaulus filaria and Protostrongylus rufescens and bacteria such as E. coli, Corynebacteriuml spp., Pasteurella haemolytica, P. multocida and Streptococcus pyogenes were diagnosed. The serological evidence of peste des petits ruminants (PPR) was confirmed in 20 animals manifesting stomatitis and glossitis.